2021
DOI: 10.3390/children8100889
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Coronavirus Pandemic on High-Risk Infant Follow-Up (HRIF) Programs: A Survey of Academic Programs

Abstract: Objective: The impact of the COVID-19 pandemic on the functioning and services of academic high-risk infant follow-up (HRIF) clinics throughout North America. Study Design: Prospective 25-question questionnaire survey through REDCAP links that was sent over 10 weeks, to 105 US and 10 Canadian programs. Finally, 59 of 105 US programs and 5 of 10 Canadian responses were analyzed using SAS version 9.4. Results: In the US, 67% of programs reported closures between 1–5 months, whereas in Canada 80% of programs clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…While most follow-up care is provided in the clinic setting, a novel transition to home programs has successfully integrated home visits after NICU discharge [25,26]. Many programs began using telehealth platforms for follow-up care during the COVID-19 pandemic [27,28]. A recent systematic review found that care coordination for infants with complex care needs reduces costs for families and health systems and leads to improved care quality [29].…”
Section: Overview Of Clinical High-risk Infant Follow-up Carementioning
confidence: 99%
“…While most follow-up care is provided in the clinic setting, a novel transition to home programs has successfully integrated home visits after NICU discharge [25,26]. Many programs began using telehealth platforms for follow-up care during the COVID-19 pandemic [27,28]. A recent systematic review found that care coordination for infants with complex care needs reduces costs for families and health systems and leads to improved care quality [29].…”
Section: Overview Of Clinical High-risk Infant Follow-up Carementioning
confidence: 99%
“…Access to health and support services, including early intervention, has grown more limited for at-risk children who are socioeconomically, culturally, and geographically disadvantaged and have developmental issues [12,13]. High-Risk Infant Follow-Up (HRIF) programs highlight the importance of monitoring the effectiveness of clinical services, which have been interrupted during the pandemic, on neonatal outcomes [14]. Pediatric emergency applications decreased by about half during the pandemic, whereas child mental health applications increased [12].…”
Section: Introductionmentioning
confidence: 99%